Mountain wildlife - Osborne, Ben.; Oxford Scientific Films (New York : Mallard Press, 1989)
Discusses mountains and the plants and animals found there.
6.9
5-8
Keywords: Alpine fauna; Alpine flora; Mountain ecology; Alpine plants; Alpine animals; Alpine plants; Alpine animals